Solid Mechanics and Its Applications
DOI: 10.1007/1-4020-4533-6_19
|View full text |Cite
|
Sign up to set email alerts
|

Surface Modification for Piston Ring and Liner

Abstract: The objectives of this paper are to numerically and experimentally investigate the potential for surface patterning and features to reduce friction at the piston ring cylinder liner interface. A test rig is used to experimentally measure the frictional loss throughout the stroke. A fully deterministic model is applied to provide explicit detail of the mixed lubrication phenomena near the dead points. The effectiveness of laser textured piston rings is examined both experimentally and numerically. Frictional pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 16 publications
2
8
0
Order By: Relevance
“…Different types of surface treatments for piston/cylinder assembly had been used to reduce the friction and wear. Nakada [98] reviewed different ways to increase Reduction of frictional losses by changing the surface roughness in the form of surface textures has been reported in case of piston rings by [4,6,9,11,13,59]. Mainly the textures created in case of piston rings are in the form of array of uniform depressions or pores with similar geometrical dimensions to one another.…”
Section: Types and Applications Of Surface Texturingmentioning
confidence: 96%
See 2 more Smart Citations
“…Different types of surface treatments for piston/cylinder assembly had been used to reduce the friction and wear. Nakada [98] reviewed different ways to increase Reduction of frictional losses by changing the surface roughness in the form of surface textures has been reported in case of piston rings by [4,6,9,11,13,59]. Mainly the textures created in case of piston rings are in the form of array of uniform depressions or pores with similar geometrical dimensions to one another.…”
Section: Types and Applications Of Surface Texturingmentioning
confidence: 96%
“…In the case of conformal contacts, If the contact has low lubricant availability, the deep dimples cause detrimental effects in terms of friction and wear [11,13]. Ryk et al [13] used reciprocating test rig to simulate the piston ring/cylinder contact.…”
Section: Dimple Depth and Diametermentioning
confidence: 99%
See 1 more Smart Citation
“…In a subsequent study, Etsion and Sher [7] compared the fuel efficiency and emission of engines equipped with partially textured and non-textured barrel shape piston rings installed in an engine and reported a 4% reduction in the fuel consumption. The effect of texturing circular dimples with different diameters and depths on the piston ring surface was studied by Bolander and Sadeghi [8]. Based on their results, textured piston rings with shallow dimples yielded a lower friction compared to deeper grooves.…”
Section: Introductionmentioning
confidence: 99%
“…They have shown that pressurization of trapped lubricant caused by deformation of a pocket under load and surface roughness in boundary and mixed lubricated contacts decrease solid contact pressure. Using numerical and experimental approaches, Nathan et al [14] investigated the potential for surface patterning and features to reduce friction at the piston ring cylinder liner interface. Meng et al [15] analyzed the influence of oil film inertia on piston skirt lubrication in a high speed engine using an iteration method.…”
Section: Introductionmentioning
confidence: 99%